Figure 2 in Mandibular biomechanics of Crocuta crocuta, Canis lupus, and the late Miocene Dinocrocuta gigantea (Carnivora, Mammalia) - Tseng, Zhijie Jack; Binder, Wendy J. (Zenodo, 2009)
Figure 2. Muscle attachment sites on the mandible finite element models, with Crocuta crocuta as an example. The light areas on top of the ascending ramus and in the mandibular fossa are attachment sites for the temporalis. The light area on the angular process is the attachment site of the masseter. The internal pterygoid attachment (not shown) is on the medial side of the angular process. Published as part of Tseng, Zhijie Jack & Binder, Wendy J., 2010, Mandibular biomechanics of Crocuta crocuta, Canis lupus, and the late Miocene Dinocrocuta gigantea (Carnivora, Mammalia), pp. 683-696 in Zoological Journal of the Linnean Society 158 (3) on page 687, DOI:10.1111/j.1096-3642.2009.00555.x, http://zenodo.org/record/5438190